Pengaruh Strategi Brand Collaboration Terhadap Purchasing Decision Pada Industri Minuman Kekinian - Anita Chrishanti Puteri Tito; Shellin Stefani (Fakultas Bisnis Universitas Mikroskil, 2023)
Indonesia’s Trendy Drinks Industry indicate an enhancement year over year. In Indonesia’s beverage market, trendy drinks are the top trend which is seen as a promising opportunity. Trendy drinks is a popular and innovative drinks which ready to drink and offer various flavors. The growth of the trendy drinks industry has created a climate of intense competition where the business needs to establish a competitive advantage. Collaboration strategy is one of strategy in the field of business that is considered the most optimal strategy. A co-Branding is a collaboration form that can be used to respond to competition. Chatime Indonesia (Chatime) is one of the trendy drinks brands that implement a collaboration strategy. The latest collaboration with BT21 offers a beverage product with various flavors, merchandise, and reusable cup for packaging. This type of research is causal exploratory to determine the cause-and-effect relationship between brand collaboration and purchasing behavior. The number of samples is about 100 respondents using the purposive sampling technique. The partial hypothesis test result (t-test) has shown that the co-branding strategy influence purchasing decision with a coefficient of determination is 0.604. In other words, the influence of co-branding strategy on purchasing decisions is 60,4%.